Influence of Add-On Perforated Plates on the ProtectivePerformance of Light-Weight Armour Systems - Teresa FRAS (Wojskowa Akademia Techniczna, 2018)
The presented experimental investigation, aimed at verification of defeat mechanisms against small-calibre projectiles, provided by 4-mm-thick perforated plates with different material- and geometrical properties, was performed. A regular pattern of punched holes in steel plates increases the possibility of asymmetrical contact between the plate and projectiles which may cause threat destabilization, rotation or fragmentation depending on the impact position. Three tested armour configurations comprise the super-bainitic high-hardness Pavise™ SBS 600P armour steel plates perforated by elongated holes of size 4 x 12 mm (the first configuration), the martensitic high-hardness Mars® 300P steel plates perforated by circular holes with a diameter of 5 mm (in the second configuration); and in the third configuration, the martensitic Mars® 300 plates perforated by oblong holes (4 x 10 mm) were used. The performed impact tests proved that the tested add-on plates assured high protection against the impact of 7.62 x 51 .308 Win P80 hard-core armour piercing (AP) projectiles. It was also observed that the plates caused similar mechanisms of bullet failure.
Keywords: Balistyka końcowa- modelowanie wnikania pocisków w metalowe, perforowane przegrody